1975
DOI: 10.1002/kin.550070314
|View full text |Cite
|
Sign up to set email alerts
|

Collisional deactivation probabilities for chemically activated 1,1,1‐trifluoroethane

Abstract: We wish to communicate results from studies of the vibrational deactivation of chemically activated molecules [ 11. The present measurements are for CHaCFZ with a wide variety of bath gases which include inefficient rare gases as well as polyatomic gases ranging up to the efficiency of those investigated by Chang, Craig, and Setser [2]. The results consist of comparisons of data at high pressure, which give a measure of relative collisional deactivation efficiencies, and of extensive low-pressure data, which p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1975
1975
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…For cyclo-CF 2 CF 2 CH 2 * colliding with CF 2 CF 2 the average energy removed per collision was 9 kcal/mol . The more exhaustive study of CF 3 CH 3 * with numerous collision partners showed that for molecules similar to our bath gas the average energy removed per collision would be 6−10 kcal/mol.…”
Section: Resultsmentioning
confidence: 91%
“…For cyclo-CF 2 CF 2 CH 2 * colliding with CF 2 CF 2 the average energy removed per collision was 9 kcal/mol . The more exhaustive study of CF 3 CH 3 * with numerous collision partners showed that for molecules similar to our bath gas the average energy removed per collision would be 6−10 kcal/mol.…”
Section: Resultsmentioning
confidence: 91%
“…Our reaction mixture is 67% SF 6 , 20% (CF 2 Cl) 2 C=O, and 13% H 2 S. Previous work suggests that for collisions involving SF 6 and (CF 2 Cl) 2 C=O with a variety of collision partners, a stepladder (SL) model with 25–42 kJ/mol removed per collision should be used for the collisional transition probability. It appears that little is known about the average energy transferred for collisions between hydrogen sulfide and either haloethanes or halomethanes, but since H 2 S comprises only 13% of our mixture we will assume that the SL model with about 32 kJ/mol (Δ E = 8 kcal/mol) removed per collision is an acceptable representation for our system.…”
Section: Resultsmentioning
confidence: 99%
“…12,13 We also simulate some of the many experiments in the literature on TFE thermal activation [14][15][16][17] and chemical activation. 18 As discussed below, we find that the KKSST data at the two highest pressures are not consistent with either RRKM theory ("standard" model) or the theoretical modification to include slow IVR ("slow-IVR" model). [7][8][9][10][11] We show that it is possible to fit the KKSST data by empirically modifying k(E) and that the same model ("truncated" model) will also fit the chemical activation data of Marcoux and Setser 19 when no constraints are placed on empirical parameters for energy transfer.…”
Section: Introductionmentioning
confidence: 86%
“…In the present paper, we address this question by determining to what extent the KKSST data are consistent with a full RRKM/master equation treatment, with the IVR theory described by Leitner and Wolynes, with a strictly empirical non-RRKM adjustment of k ( E ), and with other extant data on trifluroroethane(s). Our approach is to simulate the KKSST shock experiments with the MultiWell master equation code. , We also simulate some of the many experiments in the literature on TFE thermal activation and chemical activation …”
Section: Introductionmentioning
confidence: 99%